2011
DOI: 10.1088/0957-4484/22/30/305403
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen storage inside graphene-oxide frameworks

Abstract: In this paper, we use applied mathematical modelling to investigate the storage of hydrogen molecules inside graphene-oxide frameworks, which comprise two parallel graphenes rigidly separated by perpendicular ligands. Hydrogen uptake is calculated for graphene-oxide frameworks using the continuous approximation and an equation of state for both the bulk and adsorption gas phases. We first validate our approach by obtaining results for two parallel graphene sheets. This result agrees well with an existing theor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 39 publications
(64 reference statements)
1
45
0
Order By: Relevance
“…By adopting various linear boronic acid pillaring units, the interlayer spacing between graphene planes can be tuned to an optimum value for H 2 adsorption on both surfaces, which is twice of typical porous carbon materials and comparable to MOFs. The outstanding hydrogen storage properties are attributed to the porous spaces, and the enhanced hydrogen adsorption is mainly caused by the benzenediboronic acid pillars between graphene sheets [65]. By modulating the intercalation via three kinds of diaminoalkanes between GO layers, Kim et al [66] found an optimum GO interlayer distance of 6.3 Å with maximum H 2 uptake, similar to the predicted distance from thermally modulated GO [53].…”
Section: Physical Storage Of Hydrogenmentioning
confidence: 69%
See 1 more Smart Citation
“…By adopting various linear boronic acid pillaring units, the interlayer spacing between graphene planes can be tuned to an optimum value for H 2 adsorption on both surfaces, which is twice of typical porous carbon materials and comparable to MOFs. The outstanding hydrogen storage properties are attributed to the porous spaces, and the enhanced hydrogen adsorption is mainly caused by the benzenediboronic acid pillars between graphene sheets [65]. By modulating the intercalation via three kinds of diaminoalkanes between GO layers, Kim et al [66] found an optimum GO interlayer distance of 6.3 Å with maximum H 2 uptake, similar to the predicted distance from thermally modulated GO [53].…”
Section: Physical Storage Of Hydrogenmentioning
confidence: 69%
“…As shown in Figure 5, graphene oxide frameworks (GOFs) with 3D porosity was synthesized by intercalating the boronic acid (which can react with the hydroxyl groups) into GO layers, which showed superior hydrogen adsorption behavior [63][64][65]. By adopting various linear boronic acid pillaring units, the interlayer spacing between graphene planes can be tuned to an optimum value for H 2 adsorption on both surfaces, which is twice of typical porous carbon materials and comparable to MOFs.…”
Section: Physical Storage Of Hydrogenmentioning
confidence: 99%
“…Calculations have shown that a GO framework (GOF) which can be prepared from GO and benzenediboronic acid could be used for hydrogen adsorption (Fig. 13b), 170,171 predicting that the GOF can theoretically achieve 6.1 wt% H 2 uptake at 77 K and 1 bar. However, the experimental studies only showed a maximum uptake of 1 wt %.…”
Section: Gas Adsorptionmentioning
confidence: 99%
“…The GOFs exhibit high isosteric heat of adsorption and hydrogen adsorption capacity (twice of typical porous carbon material and comparable to MOFs). Based on the reported porous GOFs, Chan et al [45] investigated the hydrogen storage properties of GOFs (GOF-120, GOF-66, GOF-28 and GOF-6) with a mathematic model and found that the GOF-28 has highest hydrogen uptake of 6.33 wt%. The outstanding hydrogen storage properties are attributed to the porous spaces; most importantly the enhanced hydrogen adsorption is caused by the benzenediboronic acid pillars between graphene sheets.…”
Section: Go-based 3-d Framework For Hydrogen Storagementioning
confidence: 99%